2023
DOI: 10.1186/s12903-023-02867-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral status and affecting factors in Iranian ICU patients: a cross-sectional study

Abstract: Background Oral care is crucial in intensive care units (ICUs). Meanwhile, this action is not well-performed, therefore, mouth cavity-associated disorders cause serious outcomes, e.g. ventilator-dependent pneumonia. Considering a lack of studies in Iran on this subject, this study aimed to determine the oral status and affected factors in ICU patients in Iran. Methods In a cross-sectional study in 2019, we assessed the oral status of 138 patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…However, the present study found doctors rarely participated in oral care training in the ICU. Many researchers have pointed out the importance of dental professionals providing professional guidance on oral care for ICU patients [ 10 , 12 ]. The future comprehensive oral care plan should involve nurses, nursing assistants, occupational therapists, dental experts, language medical record holders, nutritionists, and rehabilitation therapists [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the present study found doctors rarely participated in oral care training in the ICU. Many researchers have pointed out the importance of dental professionals providing professional guidance on oral care for ICU patients [ 10 , 12 ]. The future comprehensive oral care plan should involve nurses, nursing assistants, occupational therapists, dental experts, language medical record holders, nutritionists, and rehabilitation therapists [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can assist with many patient-care tasks, such as personal and oral care, which greatly support the healthcare team [ 11 ]. 55.7% of nurses delegated oral care to NAs [ 12 ]. A growing number of studies focus on the oral health status of ICU patients, but relatively few investigate the perspectives and challenges of NAs in the oral care of ICU patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the present study found doctors rarely participated in oral care training in the ICU. Many researchers have pointed out the importance of dental professionals providing professional guidance on oral care for ICU patients [10,12]. The future comprehensive oral care plan should involve nurses, nursing assistants, occupational therapists, dental experts, language medical record holders, nutritionists, and rehabilitation therapists [31].…”
Section: Discussionmentioning
confidence: 99%
“…8 Decreased salivary flow consequent to medication administered favors the growth of oral pathogenic microorganisms, impacting oral health. 1,8 The dentist's assistance during hospitalization is important for oral health promotion. During this period, patients may present oral alterations locally originated by traumas, infections, and neoplasms or systemically originated by medications, basic diseases, and the patient's immunosuppression state, which may, in turn, influence the evolution of the patient's general health.…”
Section: Introductionmentioning
confidence: 99%